The effect of sacral nerve root magnetic stimulation on bladder urodynamics and M3 receptor expression in rats with neurogenic bladder - Junhua Li; Chenhao Tang; Longfei Yang; Chen Song; Yanbin Wang (IBRO Neuroscience Reports)
Objective: To investigate the effect of sacral nerve root magnetic stimulation(SMS) on bladder urodynamics and M3 receptor expression in rats with neurogenic bladder. Methods: 30 adult female SD rats were randomly divided into Normal Group, Model Group, and Magnetic Stimulation Group, with 10 rats in each group. The Model Group and Magnetic Stimulation Group used the spinal cord transtion method to establish the neurogenic bladder animal model. After successful modeling, the Magnetic Stimulation Group received magnetic stimulation treatment once per day for 8 consutive weeks. After 8 weeks, bladder urodynamics were measured under anesthesia, rats were sacrificed, and bladder detrusor muscle tissue was collected for histological and ultrastructural observation, and M3 receptor expression levels were measured. Results: The maximum bladder capacity and bladder compliance in the Magnetic Stimulation Group were higher than those in the Model Group (all P < 0. 05), and the leak point pressure was lower than that in the Model Group (P < 0. 05); there were no significant differences between the Magnetic Stimulation Group and the Normal Group in these three parameters (all P > 0. 05). H&E staining of bladder detrusor muscle tissue in the Magnetic Stimulation Group revealed minimal neutrophil infiltration. Moreover, the morphology and arrangement of the mucosal epithelial cells were closer to those observed in the Normal Group when compared with the Model Group. Under transmission electron microscopy, detrusor muscle cells had a smooth surface, slightly widened intercellular spaces, relatively uniform arrangement, and relatively intact mitochondrial structure. The expression level of M3 receptors in the bladder detrusor muscle tissue of the Magnetic Stimulation Group was significantly higher than that in the Normal Group and the Model Group (all P < 0. 05); there was no significant difference between the Model Group and the Normal Group (P > 0. 05). Conclusion: Sacral nerve root magnetic stimulation has a certain effect on improving bladder function in rats with neurogenic bladder, which may be related to the increased expression level of M3 receptors in the bladder detrusor muscle tissue.